WORKSHOP STRATEGI PEMBELAJARAN TINGKAT SEKOLAH DASAR PADA MASA PANDEMI COVID-19 DI SD NEGERI 162 PALEMBANG - Sunedi Sunedi; Marvinda Rizki Dita Dirgantara; Sylvia Lara Syaflin; Puji Ayurachmawati; Adrianus Dedy; Mega Prasrihamni; Jumiat Jumiat; Moh. Reza Ifnuari (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The Covid-19 outbreak is a more rapidly contagious disease caused by a type of coronavirus. In the country of Indonesia itself, it enforces a policy of Restricting Community Activities to suppress the spread of this virus. Even the local government implemented a lockdown policy in schools to give students a break and began implementing online learning methods (on the network). The pattern of the online learning strategy system is a distance learning system using the internet network. The purpose of this PkM is how to learn strategies for elementary school levels during the covid-19 pandemic. The partner school for this activity is SD Negeri 162 Palembang, which consists of 25 teachers. The method used is lectures and online workshops. This activity produces several strategies for learning activities that can be used by teachers as current learning strategies (Online).And the teacher has understood the use of strategies that can be used for online student learning